Yahoo Web Search

  1. Sort by

  1. LHS = -6/5 * (1 + sin(x))/cos(x) * (1 - sin(x))/(1 - sin(x)) [Multiply the top...

    3 Answers · Science & Mathematics · 09/12/2011

  2. LHS = [ ( 1 - cos 2x ) + sin 2x ] / [ ( 1 + cos 2x ) + sin 2x ] . . . .= [ ( 2 sin² x...

    2 Answers · Science & Mathematics · 12/12/2010

  3. LHS = tan²A - sin²A sin²A/cos²A - sin²A...

    1 Answers · Science & Mathematics · 15/01/2014

  4. * LHS * Since tan(x) = sin(x)/cos(x), csc(x) = 1/sin(x) and cot(x) = cos(x)/sin...

    3 Answers · Science & Mathematics · 12/06/2011

  5. LHS (sinx + tanx) / (1 + cosx) >> multiply sinx by (cosx/cosx) = [sinx(cosx/cosx) + tanx...

    2 Answers · Science & Mathematics · 04/02/2013

  6. LHS = cot(x) / (1-tan(x)) + tan(x) / (1 - cot(x)) = (1/tan(x)) / (1 - tan(x)) + tan(x...

    4 Answers · Science & Mathematics · 13/12/2007

  7. LHS: (1 - cos x)/sin x = (1 - cos x)(1 + cos x)/[sin x(1 + cos x)] = (1 - cos^2 x)/[sin x(1 + cos x)] = sin^2 x/[sin x(1 + cos x) = sin x/(1 + cos x) I think you copied it wrong.

    1 Answers · Science & Mathematics · 26/08/2011

  8. LHS = (1+cosx)/sinx = [ 1 + (2cos^2(x/2) - 1)]/2sin(x/2)cos(x/2) = 2cos^2(x/2)/2sin(x/2)cos(x/2) = cos(x/2)/cos(x/2) * cos(x/2)/sin(x/2) = 1 * cos(x/2)/sin(x/2) = cot(x/2) = RHS

    2 Answers · Science & Mathematics · 30/11/2016

  9. LHS = cos2x / (1 + sin2x) = (cos^2 x - sin^2 x) / (cos^2 x + sin^2 x + 2sin x cos x) = [(cos...

    2 Answers · Science & Mathematics · 18/12/2010

  10. LHS = [2sin²(x)cos(x)-2sin^4(x)cos(x)-cos(x)] / [cos(x)(1-sin²(x...

    1 Answers · Science & Mathematics · 22/05/2009

  1. Ad
    related to LHS
  1. Try asking your question on Yahoo Answers